Case Report: Nintedanib for immune-related pneumonitis triggered by anti-PD-1 treatment in a patient with SMARCA4-mutant NSCLC: a case report - Deng, Changwen; Deng, Ganxiu; Zhu, Xiaoping (Frontiers in Pharmacology, 2023)
SMARCA4-mutant lung cancer accounts for approximately 10% of non-small-cell lung cancers (NSCLCs), has few effective treatments, and has been associated with a poor prognosis. Our case report describes a 73-year-old man who was diagnosed with SMARCA4-mutant advanced lung adenocarcinoma. Routine driver gene mutation screening was negative, and tumor tissue immunohistochemistry analysis showed the absence of the BRG1 protein (encoded by SMARCA4). In addition to the standard chemotherapy regimens, programmed cell death protein 1 (PD-1) inhibitors were administered. After three cycles of combination therapy, the focus of the primary lung tumor shrunk evidently, but radiological interstitial abnormalities emerged in the basal and subpleural areas of the bilateral lungs. The patient’s clinical condition deteriorated and he was diagnosed with immune checkpoint inhibitor (ICI)-associated pneumonia. Thus, the combination regimen was discontinued, corticosteroid therapy was administered according to guidelines, and nintedanib was added, given that interstitial abnormalities were observed on chest computed tomography (CT). Following the above treatment, the patient’s condition improved, the standard chemotherapy regimen was restarted, and nintedanib treatment was maintained. The patient’s clinical condition continued to improve, and follow-up CT showed significant resolution of the interstitial abnormalities and stabilization of the primary tumor lesion. In summary, we report the case of a patient with SMARCA4-mutant NSCLC, which is generally considered to be associated with a poor prognosis owing to a lack of effective treatments. The patient responded favorably to initial combination therapy with ICIs, although he subsequently developed immune-related adverse events. We also found that nintedanib, a multitargeted anti-fibrotic agent, was beneficial for the treatment of immune-related lung injury and showed potential anti-tumor effects.